New genus of the subfamily Oscinellinae from Brazil (Diptera: Chloropidae) - Riccardi, Paula Raile; Bazyar, Zeinab; Lamas, Carlos Einicker (Zootaxa, 2018)
The genus Paracalamoncosis gen. nov. is described based on the species P. brasiliensis gen. nov. et sp. nov., including a brief discussion of the morphological similarities and differences with other genera in the tribe Liparaini.